Digital Spiritual Resilience: A Structural Analysis of Al-Ghazali's Tazkiyah al-Nafs as a Framework for Addressing Digital Identity Disruption Among Students - Khoirul Umam Addzaky; Uswatun Hasanah; Ida Faridatul Hasanah (Universitas Lambung Mangkurat, 2026)
This research aims to explore the concept of tazkiyah Al-Ghazali as a strategy for reconstructing the character of students in the face of digital identity disruption, with a focus on analyzing the mechanism of internalization of spiritual values and its implications for the formation of digital generation character. The research method used a qualitative approach through library research with document and literature analysis techniques, examining Al-Ghazali's works, contemporary literature on digital identity, and related academic sources. The research found that Al-Ghazali's concept of tazkiyah offers a comprehensive framework for shaping the character of learners in the digital era through four fundamental stages: muraqabah (self-surveillance), muhasabah (introspection), mu'ahadah (self-promise), and riyadhah (spiritual practice). The results revealed that this multidimensional approach is able to transform the challenges of digital identity disruption into opportunities for spiritual character development by providing effective psychological defense mechanisms in the face of virtual identity fragmentation. The research proves that Al-Ghazali's classical spiritual concept has contemporary significance, offering an integrative solution to shape an authentic, meaningful, and characterful digital generation through the internalization of sustainable spiritual values, thus bridging the Islamic intellectual tradition with the dynamics of modern technology.